Corrosion behavior of aluminum-carbon fiber/epoxy sandwich composite exposed on NaCl solution - Jáquez-Muñoz, J. M.; Castrejon, A. N.; Lira-Martínez, M. A.; Maldonado-Bandala, E.; Cabral-Miramontes, J.; Lara-Banda, M.; Estupiñán-López, F.; Nieves-Mendoza, D.; Gaona-Tiburcio, C.; Almeraya-Calderón, F. (Frontiers in Metals and Alloys, 2023)
For years the aeronautical industry has employed different types of materials to satisfy the highperformance requirements of that industry. The fiber-metals laminates (FMLs) are used due to the combination of lightweight and high mechanical properties of metal and carbon reinforced. Therefore, in this research, we made two different composites of laminate-metal and laminate-metal-laminate of CFRP and aluminum with an ALCLAD layer. The samples were characterized by salt fog (0, 48, and 96 hours) at 5 wt. % NaCl and electrochemical impedance spectroscopy (EIS) with an electrolyte of 3.5 wt. % NaCl. All the samples were studied by electron scanning microscopy (SEM). The results showed that the samples of laminate-metal-laminate presented an adsorption process after 0 and 48 hours of salt fog exposition; meanwhile, the samples of laminate-metal showed a capacitive behavior for all the samples; however, the corrosion resistance decreased when salt fog exposition time increased.